Anti-Cancer Potential of a new Derivative of Caffeic Acid Phenethyl Ester targeting the Centrosome - Giordano, Catello; Kendler, Jonatan; Sexl, Maximilian; Kollman, Sebastian; Varenicja, Maxim; Szabó, Boglárka; Timelthaler, Gerald; Kirchhofer, Dominik; Hollóczki, Oldamur; Turner, Suzanne D; Moriggl, Richard; Kenner, Lukas; et al. (Redox biology, 2025)
Anaplastic Large Cell Lymphoma (ALCL) is an aggressive T-cell lymphoma affecting children and young adults. About 30% of patients develop therapy resistance therefore new precision medicine drugs are highly warranted. Multiple rounds of structure-activity optimization of Caffeic Acid Phenethyl Ester have resulted in CM14. CM14 causes upregulation of genes involved in oxidative stress response and downregulation of DNA replication genes leading to G2/M arrest and subsequent apoptosis induction. In accordance with this, an unbiased proteomics approach, confocal microscopy and molecular modeling showed that TUBGCP2, member of the centrosomal γ-TuRC complex, is a direct interaction partner of CM14. CM14 overcomes ALK inhibitor resistance in ALCL and is also active in T-cell Acute Lymphoblastic Leukemia and Acute Myeloid Leukemia. Interestingly, CM14 also induced cell death in docetaxel-resistant prostate cancer cells thus suggesting an unexpected role in solid cancers. Thus, we synthesized and thoroughly characterized a novel TUBGCP2 targeting drug that is active in ALCL but has also potential for other malignancies.
Keywords: kyseliny kávové; protinádorové látky; nádorové buněčné linie; apoptóza; Phenylethyl Alcohol; Centrosome; Antineoplastic Agents; Apoptosis; centrozom; Humans; Cell Line, Tumor; lidé; chemorezistence; Caffeic Acids; Drug Resistance, Neoplasm; fenethylalkohol